PENGGUNAAN KETAMIN DOSIS SUB-ANESTETIK INTRAVENA DALAM MENURUNKAN KONSUMSI OPIOID PASCA OPERASI PADA PASIEN FRAKTUR KLAVIKULA DENGAN ANESTESI UMUM - Areta Feodora Effendi; M Rijal Abdillah S; Mirthanum Ruwindya; Rosmayana; Amalia Eka Putri; Betty Sunaryanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Clavicle fractures frequently require Open Reduction Internal Fixation (ORIF) under general anesthesia. Postoperative pain is commonly managed with opioids, which may cause adverse effects. Intravenous sub-anesthetic ketamine has been proposed as an opioid-sparing strategy through N-methyl-D-aspartate (NMDA) receptor blockade. Objective to analyze the effectiveness of intravenous sub-anesthetic ketamine in reducing postoperative opioid consumption in clavicle fracture patients undergoing ORIF with general anesthesia using a Laryngeal Mask Airway (LMA). Methods this prospective descriptive observational study involved five ASA I–II patients who underwent ORIF for clavicle fracture under general anesthesia with LMA at RSUD Salatiga in 2025. All patients received 75 mg intravenous ketamine during induction as part of multimodal analgesia. Hemodynamic parameters, recovery profile, Numeric Rating Scale (NRS) pain scores, additional opioid requirements, and adverse effects were observed in the recovery room. Data were analyzed descriptively. Results all patients demonstrated stable intraoperative hemodynamics without respiratory complications. LMA insertion was successful on the first attempt in all cases. Postoperative pain scores ranged from NRS 2–4 (mild pain). None of the patients required additional opioid analgesics in the recovery room. No significant adverse effects such as hallucinations, agitation, or respiratory depression were observed. Conclusion intravenous sub-anesthetic ketamine 75 mg administered during induction effectively reduced postoperative opioid requirements and provided adequate analgesia in clavicle fracture patients undergoing ORIF with general anesthesia.